2011
DOI: 10.1111/j.1548-7458.2011.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

RoundTrip: Filming a Return Home

Abstract: Visual anthropologists are aware that we can effectively use cameras (photo or video) as methodological devices. We can document events, create relationships, and present our findings in visual format. But few of us have discussed the conceptual capacity of the images we create in ethnographic research. Taking MacDougall's argument that images produce a different kind of knowledge, I use the example of a film I made about a Brazilian immigrant in Lisbon to explore how the process of filming has helped me to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…For migration scholars who wish to use filmmaking as a research tool, an important benefit is the possibility to link and compare observations of situations in the "here" and the "there" through translocal montage. Other migration scholars, too, have filmed return trips of migrants to their country of origin, and have found that filming has helped them not merely to observe, but also to conceptualize transnational migration experiences (Torresan, 2011). The contribution of Living like a common man to the field of migration studies stems from its empirically grounded commitment to middle-range theorizing -the film draws on close observations of transnational migration experiences, and uses montage to constitute an audio-visual argument about how to interpret these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…For migration scholars who wish to use filmmaking as a research tool, an important benefit is the possibility to link and compare observations of situations in the "here" and the "there" through translocal montage. Other migration scholars, too, have filmed return trips of migrants to their country of origin, and have found that filming has helped them not merely to observe, but also to conceptualize transnational migration experiences (Torresan, 2011). The contribution of Living like a common man to the field of migration studies stems from its empirically grounded commitment to middle-range theorizing -the film draws on close observations of transnational migration experiences, and uses montage to constitute an audio-visual argument about how to interpret these experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Reception studies of anthropological films have mainly dealt with two categories of audience, ''self-seeing'' audiences and ''specialized'' audiences [Baudry 1996]. With regard to self-seeing audiences, visual anthropologists have elicited reactions from informants by showing them footage of themselves, and by asking for verbal responses to their own (filmed) behavior [Banks 2001: 96-99;De Maaker 2000;Engelbrecht 1996: 171;Henley 2000: 221;Lewis 2004: 116-120;Nijland 1989;Pink 2006: 89;Postma and Crawford 2006;Torresan 2011;Vávrová 2014]. The purpose of this film elicitation technique is to distil additional information about the topic of the film that will give insights for further research and=or help in the editing process.…”
Section: Mario Rutten and Sanderien Verstappenmentioning
confidence: 99%
“…After all, David MacDougall has written, “pictures and writing produce two quite different accounts of human existence, however much filmmakers and writers strive to describe the same things” (:246). If we recognize these fundamental differences, then, as Angela Torresan has argued, anthropologists must “go beyond our preoccupations with the hierarchies between images and text to embrace the special kind of theoretical connections that we can re‐create with ethnographic films” (Torresan :119).…”
Section: Ignoring the Tourist: Film Structure And Argumentmentioning
confidence: 99%
“…Torresan, in further arguing for a more careful consideration of the possibilities of film production in anthropological research, writes, “[a film] is rather part of our process of discovering and theorizing. The new relationships it engenders, the new fiction it creates, and the new story it shows and tells are loaded with both historical and theoretical connections, even if those work mostly by inference and allusion” (:127).…”
mentioning
confidence: 99%